Sonografische Weiterbildung auf dem Weg zum radiologischen Facharzt - Weber, Marc-André; Delorme, Stefan (Der Radiologe, 2017)
IssueUltrasound is an integral part of imaging diagnostics but, unlike CT or MRI, requires the physician to have advanced technical skills for the implementation and documentation of studies.Current situationOwing to poor remuneration and the large effort required, ultrasound is not a priority at many institutions, and compared to CT, MRI or interventions, little reward is given to those committed to ultrasound. Intense practical teaching is rarely given. As a result, residents have to teach themselves or gain experience during rotations outside radiology. In some cases, they are not educated at all. Only rarely do residents in radiology participate in certified ultrasound courses, compared to other clinical disciplines.Ongoing developments(1) Standardized ultrasound curricula accompanying resident training, training focused on contrast-enhanced ultrasound, ultrasound-guided interventions, vascular ultrasound, and typical radiological applications of ultrasound like image fusion for biopsies or therapeutic interventions; (2) interdisciplinary ultrasound centers; (3) fostering of ultrasound education by the German Radiological Society (DRG) through intensive courses during the annual meeting.AchievementsThe above measures will help to increase skill and dexterity of radiologists in ultrasound, to introduce typical radiological applications of ultrasound into a broader field of applications and increase the awareness of these methods, and to strengthen the role of ultrasound in resident training.Future requirements(1) One senior radiologist in charge of ultrasound in each department; (2) communication of and adherence to examination and documentation standards; (3) demonstration of ultrasound studies during rounds and boards; (4) interdisciplinary centers for ultrasound education.
Gesehen am 28.03.2019